Stress-adaptive meander track for stretchable electronics. (8th August 2018) - Biswas, Shantonu; Reiprich, Johannes; Pezoldt, Joerg; Hein, Matthias; Stauden, Thomas; Jacobs, Heiko O
Abstract: Stretchable metallic interconnects are commonly designed using a meander-shaped metal track with a uniform width. This article reports on a ' stress-adaptive ' metal track design which varies in width to accommodate the produced torque in the metal track during stretching. The stress-adaptive design is inspired by computational and experimental studies of two conventional meander-shape metal tracks identifying a common failure mode; specifically, the propagation of torque leading to twist and mechanical fatigue. The understanding gained led to the stress-adaptive design. The stress-adaptive structure is compared with horseshoe- and U-shaped references and shows improvements in the stress distribution, levels of twist, maximum level of elongation (>320%), and required stretch and release cycles (>6000 at 150% elongation) to cause failure in a long term cycling test.